Application of Tamarillo in Entremet Cake Recipe: Innovation in Pastry Product Development - Kosasih, Silvia; Harahap, Dewi Irna Khairuna; Brian, Reagan; Wowor, Wulanmeiaya; Nurhasanah, Aan (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The purpose of the research was to find out the variations of tamarillo products, develop variations of processed tamarillo other than juice and develop pastry products. The research method starts from research steps consisting of potential and problems, collecting data, product design, product design validation, design revision, preliminary product testing, design revision and dissemination. Then proceed with phase I research methods consisting of population and sample data sources, data collection techniques, research instruments, data analysis techniques, and design validation. Then the last is the phase II research method which consists of an experimental design model to test, population and sample, data collection techniques, research instruments and data analysis techniques. The results of the research produced in the form of entremet cake products processed from tamarillo fruit. The novelty of the research is the entremet cake pastry product processed from tamarillo in the mousse and jelly section.